2006
DOI: 10.1364/oe.14.001119
|View full text |Cite
|
Sign up to set email alerts
|

Pulse properties of external-cavity mode-locked semiconductor lasers

Abstract: Abstract:The performance of an external-cavity mode-locked semiconductor laser is investigated both theoretically and experimentally. The optimization analysis focuses on the regimes of stable mode locking and the generation of sub-picosecond optical pulses. We demonstrate stable output pulses down to one picosecond duration with more than 30 dB trailing pulse suppression. The limiting factors to the device performance are investigated on the basis of a fully-distributed time-domain model. We find that ultrafa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In preceding works, it was shown that simulations based on the model agree very well with experiments regarding the mode-locking regimes and the dependence of the pulsewidth on the driving conditions [31], [34]. In this paper, we have theoretically analyzed the interplay of pulsewidth and timing jitter demonstrating the existence of an optimum optical bandwidth for the diffraction grating.…”
Section: Discussionsupporting
confidence: 65%
“…In preceding works, it was shown that simulations based on the model agree very well with experiments regarding the mode-locking regimes and the dependence of the pulsewidth on the driving conditions [31], [34]. In this paper, we have theoretically analyzed the interplay of pulsewidth and timing jitter demonstrating the existence of an optimum optical bandwidth for the diffraction grating.…”
Section: Discussionsupporting
confidence: 65%
“…The pulse widths found in this paper are on the order of 1 ps, where gain nonlinearities such as spectral hole burning and carrier heating start to play a role [13]. Following the model in [9], these effects are, however, not included here.…”
Section: Modelmentioning
confidence: 90%
“…Considering the trade-off between the two error sources, we hypothesize that there is an optimum value for the clock signal One of the most important characteristics of optical clock sources is their flexility regarding the manipulation of the clock signal. For example, [52] proposes an approach for synchronizing the mode locked laser (MLL) with a second fiber laser via an intracavity electro-optic modulator (EOM), while [53] presents a method to alter the pulse-width of the laser by manipulating the grating bandwidth, utilizing electro-optic modulation. Using these two techniques the pulse-width an appropriate frequency of the clock signal can be set to the desired values.…”
Section: Structure Of Optical Clock Recovery In An Otdm Receivermentioning
confidence: 99%